2021
DOI: 10.3390/ani11092565
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Quality and Sensory Characteristics of Spent Hen and Broiler in South Korea

Abstract: This study was conducted to compare the quality and sensory characteristics of spent hen and broiler in South Korea. The carcasses of spent hens and broilers that had been slaughtered 24 h before were used. The cooking yield and water holding capacity of broiler was significantly higher than that of spent hen (p < 0.05). The pH of broiler thigh was significantly higher than that of the other treatments (p < 0.05), while on the other hand spent hen breast had a lower value than other treatments (p < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(35 reference statements)
1
2
0
Order By: Relevance
“…This may be the reason why the cooking loss in the breast muscle was significantly higher than that in the thigh muscle; however, we did not obtain similar findings in this trial. The previous study demonstrated that a high fat content is associated with a high water-binding capacity [38]. In the current study, the thigh muscles with a higher fat content had a lower water-holding capacity in the cooked meat and a higher water-holding capacity in the raw meat, respectively, manifested as a higher cooking loss and lower dripping loss.…”
Section: Discussionsupporting
confidence: 47%
“…This may be the reason why the cooking loss in the breast muscle was significantly higher than that in the thigh muscle; however, we did not obtain similar findings in this trial. The previous study demonstrated that a high fat content is associated with a high water-binding capacity [38]. In the current study, the thigh muscles with a higher fat content had a lower water-holding capacity in the cooked meat and a higher water-holding capacity in the raw meat, respectively, manifested as a higher cooking loss and lower dripping loss.…”
Section: Discussionsupporting
confidence: 47%
“…The electronic tongue described by Lee and Kim (2021) was used with some modifications. After mixing 4 g of the sample with the casing removed and 16 mL of distilled water (DW), ultra turrax (HMZ-20DN, Pooglim Tech) was used for homogenization at a speed of 6,451×g for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…Combining sensors —while measuring the food directly was discussed extensively, indirect sensing is also very useful. For example, gas sensors could be combined with taste sensing (Li et al, 2023; Liu, Fan, et al, 2023; Ma, Shen, et al, 2023; Tian et al, 2019), or a large battery of sensors to study taste differences between chicken and hen meat (Lee & Kim, 2021). Sensor fusion gives the best resolution and variety of measurements, but is complicated and has not yet used by robots.…”
Section: Emerging Technologiesmentioning
confidence: 99%